Cold War monks : Buddhism and America's secret strategy in Southeast Asia - Ford, Eugene Brassel (Yale University Press, 2017)
"How did the U.S. government make use of a "Buddhist policy" in Southeast Asia during the Cold War despite the American principle that the state should not meddle with religion? To answer this question, Eugene Ford delved deep into an unprecedented range of U.S. and Thai sources and conducted numerous oral history interviews with key informants. Ford uncovers a riveting story filled with U.S. national security officials, diplomats, and scholars seeking to understand and build relationships within the Buddhist monasteries of Southeast Asia. This fascinating narrative provides a new look at how the Buddhist leaderships of Thailand and its neighbors became enmeshed in Cold War politics and in the U.S. government's clandestine efforts to use a predominant religion of Southeast Asia as an instrument of national stability to counter communist revolution"-- From cover flap
Keywords: Buddhism and politics -- Thailand.; Buddhism and politics -- Southeast Asia.; Buddhism -- Thailand -- History.; Buddhism -- Southeast Asia -- History.; Bouddhisme et politique -- Thaïlande.; Bouddhisme et politique -- Asie du Sud-Est.; Bouddhisme -- Thaïlande -- Histoire.; Bouddhisme -- Asie du Sud-Est -- Histoire.; RELIGION -- Comparative Religion.; HISTORY -- United States -- 20th Century.; Buddhism; Buddhism and politics; Southeast Asia; Thailand; History